2023
DOI: 10.35848/1347-4065/acb09e
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced tunable optoelectronic properties of inorganic halide perovskites APbCl3 (A = K, Rb, and Cs)

Abstract: Halide perovskites are promising photovoltaic, solar cell, and semiconductor materials. Density-functional theory (DFT) models address compressive and tensile biaxial strain effects on APbCl3, where A = (K, Rb, and Cs). This research shows how A-cation impacts bandgap energy and band structure. The direct bandgap for KPbCl3, RbPbCl3, and CsPbCl3 is found 1.612, 1.756, and 2.046 eV, respectively; increases from A=K to Cs. When spin-orbital coupling (SOC) is introduced, bandgaps in KPbCl3, RbPbCl3, and CsPbCl3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…In this research, the structural properties, electronic configurations, and optic response to electromagnetic radiation of CsPbBr 3 are examined with the use of density functional theory (DFT)-based ,, Cambridge Serial Total Energy Package (CASTEP). , Initially, the structural model of CsPbBr 3 is drawn by considering the formerly disclosed experimental parameters . To obtain the ground-state structure (optimized structure), the exchange-correlation of generalized gradient approximation (GGA) is assigned in conjunction with the extensively used functional Perdew–Burke–Ernzerhof (PBE) .…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the structural properties, electronic configurations, and optic response to electromagnetic radiation of CsPbBr 3 are examined with the use of density functional theory (DFT)-based ,, Cambridge Serial Total Energy Package (CASTEP). , Initially, the structural model of CsPbBr 3 is drawn by considering the formerly disclosed experimental parameters . To obtain the ground-state structure (optimized structure), the exchange-correlation of generalized gradient approximation (GGA) is assigned in conjunction with the extensively used functional Perdew–Burke–Ernzerhof (PBE) .…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Examining a material’s physical characteristics can assist us in comprehending the condition of a material system and reveal potential applications for a substance. For the analysis of the optical and electronic contribution of various elements in a perovskite solar absorber material, various optical and electronic properties such as band gap and band structure, density of states (DOS), and charge density distribution are essential to explore. Nowadays, scientists use the DFT technique to conduct a theoretical investigation of the physical characteristics of relevant materials. However, a few experimental and theoretical works have been found on the titled perovskite. This compound was successfully prepared by López et al using a mechanochemical process in a N 2 atmosphere, which revealed a phase transformation from orthorhombic (S.G: Pbnm , #62) to cubic (S.G: Pm 3̅ m , #221) symmetry above room temperature. It is reported that the band gap of CsPbBr 3 is possible to tune by substituting iodine in place of bromine .…”
Section: Introductionmentioning
confidence: 99%
“…However, the easier oxidation of unstable Sn 2+ ions to Sn 4+ owing to poor air stability degrades the photovoltaic performance. The search for new lead-free perovskites with excellent inherent stability for SC is still in progress and is quite challenging. Considering the toxicity of lead-based perovskites and the stability issues of the existing lead-free perovskites, the research on different lead-free inorganic perovskites has gained substantial momentum to improve the stability, optoelectronic characteristics, and eco-friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite materials have the potential to be used in highperformance photovoltaic (PV) solar cells and are receiving huge interest from the scientific community. [1][2][3][4][5] Organic-inorganic hybrid perovskite solar cells (PSCs) have achieved significant advancements in device construction and element control due to their superior optical absorption, low trap density, extended charge-carrier lifetime, high charge-carrier mobility, and low exciton binding energy. [6][7][8] However, the primary challenges for their extensive commercial uses are the volatility and thermally instability of the organic cations.…”
Section: Introductionmentioning
confidence: 99%